(untitled) (Journal of the College of Basic Education, 2023)
The current research aims to identify the perceived self-efficacy of kindergarten teachers and the differences in the perceived self-efficacy of kindergarten teachers according to the variable of academic achievement and the length of service. And the alpha coefficient and Pearson correlation coefficient) to verify the validity of the scale and extract the results of the research through the statistical bag spss. It was found that there is a semantic memory for kindergarten teachers, and there are also differences among kindergarten teachers for perceived self-efficac.